POTENSI SUMBERDAYA AIR DI SELATAN GUNUNG TAMPOMAS SELATAN KABUPATEN SUMEDANG JAWA BARAT - Garinas, Wahyu (Jurnal Teknologi Lingkungan, 2007)
Tampomas mountain areas can be divided 2 types of aquifer : volcanosediment aquifer and sediment aquifer. Volcano sediment aquifer is afree aquifer sedimentation, because there was not impermeable rockexisting under or bellow it, this aquifer also known as shallow or surfaceaquifer. Sediment aquifer is a depressed aquifer where the water flowalong the sandstone layer which covered by claystone and water flowthrough the pore. This sediment aquifer are deep aquifer. Ground waterat sumedang area can be divide as : ground water on volcanic quartersedimentation and ground water on consolidate rock.The type of water source at the reaserch area can be devide into 3 ways: Depressed water resources formed by land surface which is cuttingthe watter table, Shear water source which formed by the crack / shearstructure or sesar path, and contact water source which shown at thetertiery rock (impermeable) and quartery rock (permeable).This reaserch using geofisical methode Imaging Resistivity to resultinterpretation that on the south Tampomas Mountain predicted had 4aquifer potention resource (A,B,C,D), whith aquifer thickness vaariatedfrom (5-15)m, (30-50)m and more than 50 m. Several water sourcesurface cases found in this reaserch area at 20-30 m depth which predictas the water table. This indicated there are very large aquifer at 500 mlevel and assume this level as a potential places for ground water existat the south Tampomas mountain.